A new species of hermit crab genus Diogenes Dana, 1851 from Papua, Indonesia (Crustacea, Decapoda, Anomura, Diogenidae) - Fitrian, Tyani; Rahayu, Dwi Listyo; Ismet, Meutia Samira (Zootaxa, 2024)
A new species of hermit crab from the genus Diogenes Dana, 1851 is described on the basis of a specimen from Papua, Indonesia. Diogenes hawisi n. sp. is distinguished from the closest allied species, D. edwardsii (De Haan, 1849) and D. laevicarpus Rahayu, 1996, by the shape and armature of the left cheliped. Morphological differences of these three species are also supported by genetic analysis, through DNA barcoding using the CO1 gene marker.